Multilevel theorizing of how gender influences trust and creativity - EUN, Hye Jung (Institutional Knowledge at Singapore Management University, 2021)
Integrating the literatures on trust, gender, and creativity, this chapter takes a multilevel approach toanalyze how gender influences trust at the individual, dyadic, social network, and group levels -- which in turn leads to different creativity-related outcomes for men and women. Taking the multilevel approach allows us to discusshow trust plays a role in the gender gaps in creativity and innovation achievement. Throughout our discussion, we draw on McAllister’s (1995) affect-based trust and cognition-based trust framework, which aligns with the prior studies that document that women are primarily perceived as warm and men are largely seen as competent. Where appropriate, we also draw on scientific evidence about gender differences in social network properties, as well as the effects of gender composition in groups, to analyze gender differences in trust. In doing so, we develop a set of propositions to help explain the effect of gender on affect-based trust and cognition-based trust, as well as potential barriers and opportunities for women in creativity-related processes.